1994
DOI: 10.1002/adma.19940060108
|View full text |Cite
|
Sign up to set email alerts
|

Novel materials for non‐ablative optical recording

Abstract: Communications polyelectrolytes including poly-L-glutamate, can be explained on the basis of the model proposed by Addadi et al.L4I These authors demonstrated that the P-sheet structure of the polyaspartate adsorbed on solid substrate is essential in order to induce (001)-oriented calcite nucleation by matching the charged groups of the polymer and the intercationic distances in the crystal lattice of the salt. It follows that the [3-sheet structure should be assumed by the exposed stretches of poly-L-aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…However, the addition of cyclohexene to the mixture containing 8 does not lead to regeneration of the starting catalyst 3 with the formation of 4b and 5b in the time frame of the bromide experiments above. Studies of the thermal reductive elimination of halogen from 7 and 8 have shown that the Te−Cl bond is stronger than the Te−Br bond. , The poorer catalysis observed in the chloride reactions may be due to competitive formation of chlorine oxidative-addition products, which only slowly regenerate the Te(II) state of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…However, the addition of cyclohexene to the mixture containing 8 does not lead to regeneration of the starting catalyst 3 with the formation of 4b and 5b in the time frame of the bromide experiments above. Studies of the thermal reductive elimination of halogen from 7 and 8 have shown that the Te−Cl bond is stronger than the Te−Br bond. , The poorer catalysis observed in the chloride reactions may be due to competitive formation of chlorine oxidative-addition products, which only slowly regenerate the Te(II) state of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental verification of these predictions has come from reductive elimination and halogen exchange reactions. The bond strengths of Te(IV) dihalides have been measured by the rates of reductive elimination of halogen from Te(IV) dihalides 23 and 24 . , In these reactions, the Arrhenius energy of activation, E A , for reductive elimination of bromine from 23 is 4 kcal mol -1 lower than E A for reductive elimination of chlorine from 24 . The rates of tellurium−halogen exchange between diphenyltellurium dihalides and diphenyl telluride suggest that the bond strengths of the Te−X bonds decrease in the following order: Te−F > Te−Cl > Te−Br > Te−I .…”
Section: Discussionmentioning
confidence: 99%
“…For example, amorphous solid dispersions, drug formulations composed of active pharmaceutical ingredients dispersed in an amorphous glassy matrix, have been shown to improve important variables of biological drug efficacy such as transport and dissolution. The value of the glassy state has also been exploited for incorporating liquid crystal mesogens into low molecular weight matrices for information storage materials . Randomly organized, glassy materials have also been used as host matrices to lock in chromophore guests in the design of optoelectronic materials. More recently, small molecules have been designed for well-defined fluorescent glasses, nonlinear optics, charge transporting devices, and radioluminescence . Related to fulvenes of interest to this work, it has been reported that 1,2,3,4-tetraphenyl substituted fulvenes exhibited T g ’s of over 100 °C, and correlate with the nature of the 6-substituent (Figure ).…”
Section: Introductionmentioning
confidence: 99%